Radiographical And Clinical Features of Ameloblastoma Among Patients Visiting The Tertiary Care Hospital - Ruqqia Jehan, Talha Asher, Muhammad Adeel, Muhammad Shoaib, Muhammad Rizwan, Naima Jabeen, Asif Noor (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Odontogenic tumors derived from tooth forming apparatus, either epithelial or ecto-mesenchymal or both. Ameloblastoma is a true neoplasm of odontogenic epithelium, represent 1% of all oral ectodermal tumors and 9% of odontogenic tumors.It is a benign tumor that shows an insidious slow growth, locally invasive with high recurrence rate. Aim: To determine radiographical and clinical features of ameloblastoma in patients reporting to Oral and Maxillofacial Surgery. Study design: Descriptive Cross-Sectional Study Place and duration of study: Department of Oral and Maxillofacial surgery, Multan Medical and Dental College Multan during 6 months. Methodology: A descriptive audit including all patient records with a histopathologically confirmed report of ameloblastoma based on the routine Hematoxylin and Eosin staining during the period of 6 months. Consecutive non-probability sampling technique was used. Results: A total of 140 patient records were included in this study among whom 95 (67.9%) were male and 45(45%) were female. 123 (87.9%) lesions were found in the mandible, while 17(12.1%) in the maxilla. Swelling was the most commonly reported symptom in 137(97.9%) of the cases. Pain and tooth mobility were among other symptoms. Radiographically, the multilocular appearance accounted for 97(69.3%) while uni-loculancy was present in 43(30.7%) of the lesions. Conclusion: This study concluded that males are more affected with ameloblastoma than females. The 2nd and 3rd decades of life were the most common age group affected. Painless swelling was the most common clinical feature reported in ameloblastoma attributing to late diagnosis.